Pharyngeal perforations after anterior cervical spinal procedures: A systematic review - Baha Eldin Adam; Osman Kılıç; Selma Bozcan; Mehmet Ali Kahraman; Abdullah Talha Şimşek; Fatih Çalış; Ahmet Mutlu; Naci Balak (Heliyon)
Background: Digestive system perforations after anterior cervical spine surgery (ACSS), if left untreated, are life-threatening. These injuries are often categorized as pharyngoesophageal. Although the pharynx and esophagus are continuations of each other, they are two distinct anatomical structures. There is limited experience in managing patients with pharyngeal injuries after ACSS. Methods: Using PRISMA guidelines, a PubMed search was conducted on the iatrogenic pharyngeal perforations after ACSS for the treatment of disc herniation and degenerative cervical myeloradiculopathy. Results: A total of 12 patients met our inclusion criteria. Eleven were from published studies, and one was our patient (2 female and 10 male, mean age = 56.25 years, range: 31–82 years). Clinical symptoms of patients with iatrogenic pharyngeal perforation after ACSS varied depending on whether the cases present early or late after surgery. Although clinical symptoms suggested a pharynx or esophageal injury, definitive diagnosis was challenging. All cases diagnosed either early or late after ACSS underwent surgical repair treatment, except for one case managed conservatively with antibiotics and nasogastric feeding. The overall outcome was favorable for all patients. However, the postoperative follow-up duration was not specified in two cases. In the remaining 10 cases, postoperative follow-up durations were generally short and varied significantly (mean = 4.87 months, median = 1.75 months, range:1 week–24 months). Conclusion: Iatrogenic pharyngeal injuries resulting from ACSS are extremely rare. They are relatively straightforward to diagnose and can be managed with a multidisciplinary approach. However, their long-term prognosis remains unknown.